Device
The device with a polymer-coated, irregularly shaped particle protrusions effectively addresses inefficiencies in extracellular vesicle separation by enhancing trapping strength and efficiency, achieving high capture rates and miRNA recovery.
Patent Information
- Application Number
- JP2023095539
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-19
AI Technical Summary
Existing methods for separating extracellular vesicles from body fluids are inefficient, requiring large sample volumes, long separation times, and result in low recovery rates and decreased marker protein amounts, with conventional devices lacking sufficient protrusion strength for effective trapping.
A device with a coating layer containing irregularly shaped particles buried in a polymer layer, forming protrusions with specific dimensions and materials, enhances the strength and efficiency of extracellular vesicle trapping.
The device achieves high extracellular vesicle capture rates, up to 94.9%, and recovers significant amounts of miRNA, demonstrating improved efficiency and strength in capturing biological samples.
Smart Images

Figure 2024176757000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a device. [Background technology]
[0002] Disease testing using bodily fluids such as urine and blood is called liquid biopsy, and is attracting attention as a new testing method. Extracellular vesicles released by cells contain microRNA (microribonucleic acid; hereafter sometimes referred to as "miRNA"), which functions as an early diagnostic marker for cancer, and there is a demand for technology to capture extracellular vesicles.
[0003] Existing methods for separating extracellular vesicles include ultracentrifugation and agglutination reagent methods. The most commonly used ultracentrifugation method requires several tens of mL of sample volume and 4 to 5 hours of separation time, and the recovery rate is about 5 to 25%, making it difficult to efficiently separate extracellular vesicles. The agglutination reagent method is a simple method in which an agglutination reagent is dropped onto the target sample and allowed to stand, but it requires a long period of standing for separation and has problems such as the use of a centrifuge, changes in particle size, a decrease in the number of particles, and a decrease in the amount of marker protein.
[0004] To solve the above problems, a method has been reported in which extracellular vesicles from small amounts of body fluid or culture supernatant are adsorbed onto nanowires formed in the microchannels of a chip, enabling highly efficient extraction of miRNA derived from extracellular vesicles (see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6606786 Summary of the Invention [Problem to be solved by the invention]
[0006] While forming protrusions on the surface makes it easier to collect extracellular vesicles, there was room for improvement in the strength of the protrusions in conventional devices with protrusions.
[0007] An object of the present invention is to provide a device having projections on its surface which are strong and have a high efficiency of capturing extracellular vesicles. [Means for solving the problem]
[0008] As a result of extensive research to achieve the above-mentioned objective, the inventors discovered that the above-mentioned problems could be solved by a device having a coating layer in which a portion of a specific shaped irregular particle is embedded in a polymer layer, thereby completing the present invention.
[0009] That is, the respective aspects of the present invention are [1] to
[14] shown below. [1] A device comprising a supporting substrate and a coating layer formed on the supporting substrate, the coating layer including a polymer layer and irregularly shaped particles, the irregularly shaped particles having portions embedded in the polymer layer and portions exposed from the polymer layer, and the exposed portions from the polymer layer forming protrusions on a surface of the coating layer opposite the supporting substrate. [2] The device according to [1], wherein the major axis of the irregular-shaped particles is 0.1 to 100 μm, the minor axis of the irregular-shaped particles is 0.01 to 10 μm, and the ratio of the major axis of the irregular-shaped particles to the minor axis of the irregular-shaped particles is 2.0 or more. [3] The device according to [1] or [2], wherein a ratio of the height of the protrusions to the major axis of the irregularly shaped particles is 0.10 to 0.95. [4] The device according to any one of [1] to [3], wherein when the coating layer is viewed from the side where the protrusions are present, the area of the region where the protrusions are present accounts for 10% or more of the entire coating layer. [5] The device according to any one of [1] to [4], wherein the number of the irregular-shaped particles that do not have a portion embedded in the polymer layer is 50% or less of the total number of the irregular-shaped particles. [6] The device described in any one of [1] to [5], wherein the length in the out-of-plane direction of the supporting substrate from the surface of the supporting substrate facing the coating layer to the apex of the protrusion is equal to or less than the major axis of the irregularly shaped particle. [7] The device according to any one of [1] to [6], wherein the protrusions are oriented in one direction. [8] The device according to any one of [1] to [7], wherein the material of the irregularly shaped particles is selected from the group consisting of silica, zinc oxide, titanium oxide, nickel oxide, alumina oxide, yttria oxide, tin oxide, indium oxide, indium tin oxide, silicon carbide, gold, silver, carbon, silicon nitride, and combinations thereof. [9] The device described in any one of [1] to [8], wherein the irregularly shaped particles are surface-modified with a silane coupling agent at least at the embedded portion, and the difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer layer is 5 or less.
[10] The device according to any one of [1] to [9], wherein the protrusions are covered with a coating layer containing at least one selected from the group consisting of zinc oxide, titanium oxide, nickel oxide, yttria oxide, tin oxide, alumina oxide, silica, indium oxide, and indium tin oxide.
[11] The device according to any one of [1] to
[10] , wherein the protrusions are covered with a coating layer containing a cationic polymer.
[12] The device described in any of [1] to
[11] , further comprising a coated substrate having one or more through holes on the side of the coating layer opposite the supporting substrate, and at least one of the through holes forms a space for adding a biological sample.
[13] The device described in
[12] , further comprising an intermediate layer between the coating layer and the coated substrate, the intermediate layer including an area for adhering the coating layer to the coated substrate and an internal space forming a flow path for transporting the biological sample.
[14] The device according to any one of [1] to
[13] , which is for collecting a biological sample. Effect of the Invention
[0010] According to the present invention, it is possible to provide a device having protrusions on its surface that are strong and have a high efficiency of capturing extracellular vesicles. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view of the device. [Diagram 2] FIG. 2 is a schematic diagram showing buried and exposed portions of an irregularly shaped particle. [Diagram 3] FIG. 3 is a schematic diagram showing the major and minor axes of irregular-shaped particles. [Figure 4] FIG. 4 is a perspective view showing an example of a device in the form of a well plate. [Diagram 5] FIG. 5 is a perspective view showing an example of a flow channel configuration device. [Figure 6] FIG. 6 is a scanning electron microscope photograph of the surface of the device of Example 1. [Figure 7] FIG. 7 is a scanning electron microscope photograph of the surface of the device of Example 2. [Figure 8] FIG. 8 is a scanning electron microscope photograph of the surface of the device of Example 3. [Figure 9] FIG. 9 is a scanning electron microscope photograph of the surface of the device of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiment of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following embodiment. In this specification, "(meth)acryloyl group" refers to a methacryloyl group or an acryloyl group, and "(meth)acrylate" refers to a methacrylate or an acrylate. Unless otherwise specified, the materials exemplified below may be used alone or in combination of two or more.
[0013] Fig. 1 shows one embodiment of the device. The device 10 shown in Fig. 1 comprises a support substrate 1 and a coating layer 2 formed on the support substrate 1. The coating layer 2 includes a polymer layer 3 and irregularly shaped particles 4. As shown in Fig. 2, the irregularly shaped particles 4 have portions 4a embedded in the polymer layer 3 and portions 4b exposed from the polymer layer 3. The irregularly shaped particles 4 are fixed to the polymer layer 3 by the portions 4a embedded in the polymer layer 3. Protrusions 5 are formed on the surface of the coating layer 2 opposite to the support substrate 1 by the portions 4b exposed from the polymer layer 3.
[0014] The device 10 can be suitably used as a device for collecting biological samples. As used herein, a "biological sample" is a sample obtained from an animal (e.g., a human) or a plant. Examples of biological samples include urine, blood, tissue, cells, and extracellular vesicles. These biological samples may contain DNA, RNA (e.g., miRNA), proteins, and the like.
[0015] <Supporting base material> The material of the supporting substrate 1 is not particularly limited, and examples thereof include resin, glass, ceramics, etc. The supporting substrate 1 may be a substrate of any shape, such as a film, a sheet, a plate, or a structure having a curved surface.
[0016] Resins that can be used as the supporting substrate 1 include cellulose-based resins such as triacetyl cellulose, diacetyl cellulose, and acetate butyrate cellulose; polyester resins such as polyethylene terephthalate; polycarbonate resins; acrylic resins such as polymethyl methacrylate; polyurethane resins; polyether resins; polysulfone resins; polyethersulfone; polyether ketone, and the like.
[0017] A coating layer such as a hard coat layer, an anchor coat layer, or a polymer electrolyte layer may be formed on the surface of the supporting substrate 1 in order to improve scratch resistance and adhesion, and surface treatment such as UV ozone cleaning, plasma treatment, or corona treatment may be performed in order to improve adhesion and coatability.
[0018] <Coating layer> The coating layer 2 is provided on the main surface of the supporting substrate 1. The coating layer 2 includes a polymer layer 3 and irregularly shaped particles 4.
[0019] (polymer layer) The polymer layer 3 contains a polymer. The polymer layer 3 fixes the irregularly shaped particles 4 at the embedded portions 4a, thereby increasing the strength of the protrusions 5 formed by the exposed portions 4b.
[0020] Examples of the polymer include poly(meth)acrylates such as polymethyl(meth)acrylate and poly(ethyl)acrylate, polytrimethylolpropane ethoxy tri(meth)acrylate, polypentaerythritol ethoxy tetra(meth)acrylate, polytrimethylolpropane propoxy tri(meth)acrylate, polypentaerythritol tri(meth)acrylate, polypentaerythritol tetra(meth)acrylate, polydipentaerythritol hexa(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytricyclodecane dimethanol di(meth)acrylate, and polyethoxylated phenyl (meth)acrylate. aliphatic polymers such as polystyrene, poly-α-methylstyrene, polyvinyltoluene, poly-p-methylstyrene, poly-2-methylstyrene, poly-3-methylstyrene, poly-4-methylstyrene, poly-4-ethylstyrene, poly-4-tert-butylstyrene, poly-3,4-dimethylstyrene, poly-4-methoxystyrene, poly-4-ethoxystyrene, poly-2-chlorostyrene, poly-3-chlorostyrene, poly-4-chlorostyrene, poly-2,4-dichlorostyrene, poly-2,6-dichlorostyrene, poly-4-chloro-3-methylstyrene, polydivinylbenzene, poly-1-vinylnaphthalene, poly-2-vinylpyridine, poly-4-vinylpyridine, poly-sodium p-styrenesulfonate, and other aromatic polymers.
[0021] In view of availability, the polymer preferably includes one selected from the group consisting of polymethyl(meth)acrylate and polystyrene.
[0022] The polymer may be a homopolymer obtained by polymerization of a single corresponding monomer, or a copolymer obtained by polymerization of a mixture of several monomers. When obtaining a polymer by polymerization of a monomer, various additives may be used as necessary. Examples of additives include initiators, antioxidants, polymerization inhibitors, leveling agents, and silane coupling agents. When obtaining a polymer by polymerization of a monomer, it is preferable to use an initiator. Examples of initiators include potassium peroxodisulfate, hydrogen peroxide, azobisisobutyronitrile, and benzoyl peroxide.
[0023] The solubility parameter of the polymer may be 7 or more, 8 or more, or 9 or more, and may be 12 or less, 11 or less, or 10 or less.
[0024] (unusual particles) The irregularly shaped particles 4 are particles having shape anisotropy. "Having shape anisotropy" means that the shape is other than a sphere and other than a regular polyhedron.
[0025] The major axis of the irregular-shaped particle 4 refers to the maximum particle size of the irregular-shaped particle 4. The minor axis of the irregular-shaped particle 4 refers to the maximum particle size in the direction perpendicular to the axis (major axis) of the major axis of the irregular-shaped particle 4. The major axis and minor axis of the irregular-shaped particle 4 can be calculated by measuring these lengths on a scanning electron microscope photograph. Figure 3 shows an example of an irregular-shaped particle 4, where L indicates the major axis and S indicates the minor axis.
[0026] The major axis of the irregular-shaped particles 4 is preferably 0.1 to 100 μm, since it is possible to expose the irregular-shaped particles 4 from the polymer layer 3 while partially embedding the irregular-shaped particles 4 in the polymer layer 3, and it is possible to balance the strength of the protrusions 5 with the performance of capturing a biological sample. The major axis of the irregular-shaped particles 4 is preferably 0.2 μm or more, 0.5 μm or more, 1.0 μm or more, 2.0 μm or more, 3.0 μm or more, 4.0 μm or more, 5.0 μm or more, 8.0 μm or more, or 10.0 μm or more, since this is suitable for improving the performance of capturing a biological sample. The major axis of the irregularly shaped particles 4 is preferably 80.0 μm or less, 50.0 μm or less, 30.0 μm or less, 20.0 μm or less, 15.0 μm or less, 12.0 μm or less, 10.0 μm or less, 8.0 μm or less, 6.0 μm or less, 5.0 μm or less, 3.0 μm or less, or 1.0 μm or less, since this is suitable for improving the strength of the protrusions 5.
[0027] The minor axis of the irregular-shaped particle 4 is preferably 0.01 to 10 μm, since the strength of the irregular-shaped particle 4 can be improved, while the surface area of the protrusions 5 can be increased to improve the performance of capturing a biological sample by increasing the strength of the irregular-shaped particle 4. The minor axis of the irregular-shaped particle 4 is preferably 0.02 μm or more, 0.04 μm or more, 0.05 μm or more, 0.10 μm or more, or 0.15 μm or more, since it is suitable for increasing the strength of the protrusions 5, and may be 1.0 μm or more or 5.0 μm or more. The minor axis of the irregular-shaped particle 4 is preferably 8.0 μm or less, 4.0 μm or less, 2.0 μm or less, 1.0 μm or less, 0.50 μm or less, 0.40 μm or less, or 0.30 μm or less, since it is suitable for improving the performance of capturing a biological sample.
[0028] The ratio (L / S) of the major axis (unit: μm) to the minor axis (unit: μm) of the irregularly shaped particle 4 is preferably 2.0 or more, since both the embedded portion 4a of the irregularly shaped particle 4 in the polymer layer 3 and the exposed portion 4b from the polymer layer 3 can be lengthened, and both the strength of the protrusions 5 and the performance of capturing a biological sample can be achieved, and more preferably 3.0 or more, 4.0 or more, 5.0 or more, 8.0 or more, 10.0 or more, 15.0 or more, 20.0 or more, 25.0 or more, 50.0 or more, 75.0 or more, or 100.0 or more, since this is more suitable for improving the strength of the protrusions 5 and the performance of capturing a biological sample. The ratio of the major axis to the minor axis of the irregularly shaped particle 4 may be 150.0 or less, 125.0 or less, 100.0 or less, 75.0 or less, 50.0 or less, 30.0 or less, or 25.0 or less.
[0029] The material of the irregular shaped particles 4 is not particularly limited, but examples thereof include silica, zinc oxide, titanium oxide, nickel oxide, alumina oxide, yttria oxide, tin oxide, indium oxide, indium tin oxide, silicon carbide, gold, silver, carbon, and silicon nitride, in view of the ease of synthesis of the irregular shaped particles 4. The material of the irregular shaped particles 4 preferably contains at least one selected from the group consisting of zinc oxide, titanium oxide, alumina oxide, silica, and combinations thereof, in view of the particular ease of synthesis of the irregular shaped particles 4, and particularly preferably contains at least one selected from the group consisting of zinc oxide and titanium oxide.
[0030] The irregularly shaped particles 4 may be surface-modified with a silane coupling agent, and at least the portions 4a embedded in the polymer layer 3 may be surface-modified with a silane coupling agent.
[0031] The silane coupling agent may have a reactive functional group such as an ethylenically unsaturated group (e.g., a vinyl group, a (meth)acryloyl group), an epoxy group, an amino group, an isocyanurate group, an isocyanate group, a ureido group, a mercapto group, or a polysulfide group (e.g., a tetrasulfide group).
[0032] Examples of silane coupling agents having a (meth)acryloyl group include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane. Examples of silane coupling agents having a vinyl group include vinyltrimethoxysilane, vinyltriethoxysilane, and p-styryltrimethoxysilane. Examples of silane coupling agents having an epoxy group include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-glycidoxypropyltrimethoxysilane. Examples of silane coupling agents having an amino group include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane. An example of a silane coupling agent having an isocyanurate group is tris-(trimethoxysilylpropyl)isocyanurate. An example of a silane coupling agent having an isocyanate group is 3-isocyanatepropyltriethoxysilane. An example of a silane coupling agent having an ureido group is 3-ureidopropyltrialkoxysilane. An example of a silane coupling agent having a mercapto group is 3-mercaptopropylmethyldimethoxysilane. An example of a silane coupling agent having a polysulfide group is bis(triethoxysilylpropyl)tetrasulfide.
[0033] The silane coupling agent is preferably a silane coupling agent having a (meth)acryloyl group.
[0034] The difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer is preferably 5 or less. The small difference in solubility parameter between the component constituting the surface of the irregularly shaped particle 4 at the buried portion 4a in the polymer layer 3 and the polymer increases the compatibility between the irregularly shaped particle 4 and the polymer, making it difficult for the irregularly shaped particle 4 to detach from the polymer layer 3. As a result, the strength of the protrusion 5 can be further increased. Since it is suitable for increasing the strength of the protrusion 5, the difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer is more preferably 4 or less, even more preferably 3 or less, and most preferably 2 or less. In this specification, the Hansen solubility parameter (HSP value) is used as the value of the solubility parameter.
[0035] The solubility parameter of the silane coupling agent may be 10 or more, 11 or more, or 12 or more, and may be 15 or less, 14 or less, or 13 or less.
[0036] The degree of dispersion (polydispersity index), which is an index of particle size distribution of irregularly shaped particles, is preferably 10% or less, more preferably 8% or less, and particularly preferably 5% or less, since this is suitable for suppressing the variation of the protrusions 5 in the coating layer 2 and keeping the amount of the biological sample collected constant. In this specification, the "degree of dispersion" is measured by dynamic light scattering, and the polydispersity index obtained by the cumulants method is used as the degree of dispersion.
[0037] The content of the irregular-shaped particles 4 may be 1.0 parts by mass or more, 2.0 parts by mass or more, 3.0 parts by mass or more, 3.5 parts by mass or more, 7.0 parts by mass or more, or 15.0 parts by mass or more, and may be 20 parts by mass or less, 15.0 parts by mass or less, 10.0 parts by mass or less, 8.0 parts by mass or less, 6.0 parts by mass or less, or 5.0 parts by mass or less, relative to 1 part by mass of the total amount of the polymer. When the irregular-shaped particles 4 are surface-modified with a silane coupling agent, the total content of the irregular-shaped particles 4 and the silane coupling agent may be within the range described above as the content of the irregular-shaped particles 4.
[0038] (covering layer) At least a part of the side of the coating layer 2 on which the protrusions 5 are present may or may not be covered with a coating layer. It is preferable that at least the protrusions 5 of the coating layer 2 are covered with a coating layer.
[0039] The coating layer may be, for example, an inorganic oxide layer or an ionic polymer layer. When the coating layer is an inorganic oxide layer or an ionic polymer layer, it is possible to further increase the capture rate of extracellular vesicles.
[0040] The inorganic oxide layer contains an inorganic oxide, such as zinc oxide (ZnO), alumina oxide (Al2O3), silica (SiO2), nickel oxide (NiO), titanium oxide (TiO2), yttria oxide (Y2O3), tin oxide (e.g., SnO), indium oxide, and indium tin oxide (ITO).
[0041] Since the inorganic oxide layer is suitable for increasing the capture rate of extracellular vesicles, it preferably contains at least one selected from the group consisting of zinc oxide, alumina oxide, silica, nickel oxide, titanium oxide, yttria oxide, tin oxide, and indium tin oxide, and more preferably contains at least one selected from the group consisting of zinc oxide, titanium oxide, and indium tin oxide.
[0042] The method for forming an inorganic oxide layer on the surface of the coating layer 2 is not particularly limited, but examples include a method in which the desired inorganic oxide is directly coated by sputtering, chemical vapor deposition, deposition, etc., and a method in which a precursor of the inorganic oxide is wet-coated and then grown into the inorganic oxide by a sol-gel method.
[0043] The ionic polymer layer may contain a cationic polymer and / or an anionic polymer. The cationic polymer is preferably a polymer containing a secondary amino group, a tertiary amino group, or a quaternary ammonium group. Examples of the cationic polymer include polyelectrolytes such as polyethyleneimine and its quaternary derivatives, polydiallyldimethylammonium chloride, poly(N,N'-dimethyl-3,5-dimethylene-piperidinium chloride) polyallylamine and its quaternary derivatives, polydimethylaminoethyl(meth)acrylate and its quaternary derivatives, and polydimethylaminopropyl(meth)acrylamide and its quaternary derivatives.
[0044] Anionic polymers are -COOH, -COO - , -SO3H, or -SO3 - Examples of the anionic polymer include poly(meth)acrylic acid and its ionized products, poly(sodium polystyrenesulfonate), poly(2-acrylamido-2-methyl-1-propanesulfonic acid), polyamic acid, and poly(potassium vinylsulfonate).
[0045] The ionic polymer layer preferably contains a cationic polymer, since it is possible to further increase the extracellular vesicle capture rate. The ionic polymer layer preferably contains a cationic polymer and does not contain an anionic polymer (cationic polymer layer), or contains a cationic polymer and an anionic polymer, since it is possible to further increase the extracellular vesicle capture rate.
[0046] The method of forming an ionic polymer layer on the surface of the coating layer 2 is not particularly limited, and can be appropriately selected depending on the material of the irregularly shaped particles 4 and the types of cationic polymer and anionic polymer. For example, a method including surface-treating the surface of the coating layer 2 on which the protrusions 5 are provided, and attaching a liquid containing a cationic polymer or anionic polymer to the surface-treated surface of the coating layer 2, washing with water or the like as necessary, and then drying can be used. For example, plasma treatment can be used for the surface treatment. For example, a method of forming an ionic polymer layer containing a cationic polymer and an anionic polymer on the surface of the coating layer 2 can be used, in which the surface of the coating layer 2 is coated with one of the cationic polymer and the anionic polymer, and then coated with the other polymer.
[0047] The thickness of the coating layer may be 50 nm or more, 80 nm or more, or 90 nm or more, and may be 200 nm or less, 160 nm or less, 120 nm or less, or 110 nm or less. The thickness of the coating layer can be measured by the following method. The support substrate 1 on which the coating layer 2 having the coating layer on its surface is formed is cut with a microtome to prepare a thin film slice. The slice is observed with a scanning electron microscope, and the length from the interface between the coating layer 2 and the coating layer to the surface of the coating layer is measured.
[0048] The height of the protrusions 5 may be 0.10 μm or more, 0.30 μm or more, 0.50 μm or more, 0.80 μm or more, 1.00 μm or more, 1.50 μm or more, 2.00 μm or more, or 2.50 μm or more, and may be 8.00 μm or less, 6.00 μm or less, 4.00 μm or less, or 3.50 μm or less. The height of the protrusions 5 can be calculated by observing the cross section of the coating layer 2 with a scanning electron microscope and determining the length in the out-of-plane direction of the support substrate 1 from the surface of the polymer layer 3 on which the protrusions 5 are provided to the apex of the protrusions 5.
[0049] The ratio of the height (unit: μm) of the protrusions 5 to the major axis (unit: μm) of the irregular-shaped particles 4 (height of the protrusions 5 / major axis of the irregular-shaped particles 4) is preferably 0.10 to 0.95. By having the ratio of the height of the protrusions 5 to the major axis of the irregular-shaped particles 4 in the above range, it is possible to achieve both the strength of the protrusions 5 and the performance of capturing a biological sample. Since it is suitable for improving the performance of capturing a biological sample, it is preferable that the ratio of the height of the protrusions 5 to the major axis of the irregular-shaped particles 4 is 0.20 or more, 0.30 or more, 0.50 or more, 0.60 or more, 0.70 or more, or 0.80 or more. Since it is suitable for increasing the strength of the protrusions 5, it is preferable that the ratio of the height of the protrusions 5 to the major axis of the irregular-shaped particles 4 is 0.90 or less, 0.85 or less, 0.80 or less, 0.75 or less, or 0.70 or less, and may be 0.60 or less, or 0.40 or less.
[0050] When the coating layer 2 is viewed from the side where the protrusions 5 are present, the ratio of the area of the region where the protrusions 5 are present to the entire coating layer 2 (hereinafter also referred to as the "protrusion presence ratio") is preferably 10% or more. When the protrusion presence ratio is 10% or more, the performance of capturing a biological sample can be improved. Since this is suitable for improving the performance of capturing a biological sample, the protrusion presence ratio is preferably 30.0% or more, 50.0% or more, 60.0% or more, 70.0% or more, or 80.0% or more. The protrusion presence ratio may be, for example, 100.0% or less, 95.0% or less, 90.0% or less, or 85.0% or less.
[0051] The protrusion presence ratio can be determined by observing the surface of the coating layer 2 on which the protrusions 5 are present with a scanning electron microscope from a direction perpendicular to the surface, and dividing the area in the obtained scanning electron microscope image in which the protrusions 5 (irregularly shaped particles 4 exposed from the polymer layer 3) are present by the area of the measurement range. Here, the measurement range is a range equivalent to the area of a square with one side 100 times or more the minor axis of the irregularly shaped particles 4 that form the protrusions 5. Details of the measurement method may be as described in the examples.
[0052] In the coating layer 2, the number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 is preferably 50% or less of the total number of irregular-shaped particles 4. By making the number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 50% or less of the total number of irregular-shaped particles 4, contamination of the irregular-shaped particles 4 due to inclusion when the biological sample is contacted can be suppressed. Since it is suitable for suppressing contamination of the biological sample due to inclusion of the irregular-shaped particles 4, the number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 is more preferably 30% or less of the total number of irregular-shaped particles 4, further preferably 10% or less, and most preferably 5% or less. The number of irregular-shaped particles 4 that do not have an embedded portion 4a in the polymer layer 3 can be obtained by immersing the biological sample collection device in pure water and irradiating it with ultrasonic waves to peel off and recover the particles from the device, and the number of particles can be measured. In addition, the total number of irregular-shaped particles 4 contained in the coating layer 2 can be determined by recovering the irregular-shaped particles 4 after removing the polymer layer 3 by washing with a solvent or by baking, and counting the number of particles.
[0053] The length in the out-of-plane direction of the supporting substrate 1 from the surface of the supporting substrate 1 facing the coating layer 2 to the apex of the protrusion 5 is suitable for increasing flexibility, and is therefore preferably 10 times or less the major axis of the irregularly shaped particles 4, 5 times or less the major axis of the irregularly shaped particles 4, or 2 times or less the major axis of the irregularly shaped particles 4, and more preferably less than the major axis of the irregularly shaped particles 4. When the length in the out-of-plane direction of the supporting substrate 1 from the surface of the supporting substrate 1 facing the coating layer 2 to the apex of the protrusion 5 is less than the major axis of the irregularly shaped particles 4, the thickness of the coating layer 2 can be made thin, resulting in a device with particularly excellent flexibility.
[0054] In the application of collecting cells, it is preferable that the protrusions 5 formed by the exposed irregularly shaped particles 4 are oriented in one direction. In the case of a device having a flow channel structure, the protrusions 5 are oriented in one direction, and by arranging the protrusions 5 against the flow of the biological sample in the flow channel, the capture efficiency of the biological sample by the protrusions 5 can be increased. In addition, in the case of biological samples such as cells, the components inside the biological sample can be easily extracted by crushing them with the protrusions. The orientation of the protrusions 5 in one direction can be determined by the presence or absence of bright spots in the Fourier transform image obtained by measuring a scanning electron microscope image of the device surface and Fourier transforming the image. By the Fourier transform, it is possible to convert the shading of the original image into a two-dimensional image representing the power (square of the absolute value of the brightness) for the wave number of each sine wave when the shading of the original image is approximated by superimposing sine waves, and if there is regularity in the shading of the original image, bright spots corresponding to each sine wave will appear in the Fourier transform image.
[0055] In applications for capturing extracellular vesicles, it is preferable that the protrusions 5 formed by the exposed irregularly shaped particles 4 are irregularly arranged. By having the protrusions 5 formed by the exposed irregularly shaped particles 4 be irregularly arranged rather than oriented in one direction, in the case of a device having a flow channel structure, the reproducibility of the capture efficiency of the biological sample can be stabilized without depending on the direction of the protrusions 5 in the flow channel.
[0056] The device 10 may further include a coated substrate having one or more through-holes on the surface of the coating layer 2 opposite to the support substrate 1. The device may have a space for adding a biological sample formed by at least one of the through-holes.
[0057] FIG. 4 shows an example of a device further comprising a coated substrate, which is a well plate type device. The device 10A shown in FIG. 4 comprises a support substrate 1, a coating layer 2, and a coated substrate 6. The coated substrate 6 has a plurality of spaces 7. In the device 10A, the spaces 7 are formed for adding biological samples. Since the spaces 7 are separated from the other spaces, different biological samples can be added to each space in one device without mixing the biological samples. Therefore, the device 10A can handle multiple types of biological samples at the same time. The spaces 7 may be through-holes, since this promotes the reaction of the biological samples.
[0058] The number of spaces 7 in the coated substrate 6 may be 2 or more. The number of spaces 7 in the coated substrate 6 is preferably, for example, 6, 24, 48, 96, 384, or 1536. The spaces 7 may also be 2 or more through holes.
[0059] Fig. 5 shows an example of a device further including an intermediate layer 8, which is a device having a flow path. In device 10B shown in Fig. 5, a supporting substrate 1, a coating layer 2, an intermediate layer 8, and a coated substrate 6 are laminated in this order.
[0060] Two spaces 7a, 7b are formed in the coated substrate 6. The spaces 7a, 7b are through holes. One space 7a is a space for adding a liquid containing a biological sample, and the other space 7b is a space for recovering the liquid. Since the liquid added to one space 7a flows out into the other space 7b after passing through the flow path, the liquid from which at least some of the components in the biological sample have been removed can be recovered.
[0061] The intermediate layer 8 is disposed between the coating layer 2 and the coated substrate 6, and includes an area for bonding the coating layer 2 to the coated substrate 6, and an internal space that forms a flow path 9 for transporting a biological sample.
[0062] The flow path 9 has a central region and two end regions, and the two end regions are arranged so as to be located vertically below the spaces 7a and 7b, respectively. The intermediate layer 8 can be formed, for example, from an adhesive tape. In this case, the coating layer 2 and the coated substrate 6 are bonded together with the adhesive tape, and the flow path 9 can be formed by using the region where the adhesive tape is not present as an internal space.
[0063] The biological sample is added onto the coating layer 2 in the end region of the flow channel 9 through the space 7a. The added biological sample is transported to the space 7b along the direction d while contacting the protrusions 5 in the coating layer 2. According to the device 10B, the biological sample can be brought into contact with the coating layer 2 in a minute space, and components can be efficiently extracted even from a small amount of biological sample.
[0064] The device according to this embodiment has an improved extracellular vesicle capture rate. The extracellular vesicle capture rate is preferably 50% or more, more preferably 60% or more, particularly preferably 80% or more, and most preferably 90% or more. The extracellular vesicle capture rate is calculated by the following formula 1. Details of the measurement method are as described in the Examples below. Formula 1: ([Amount of extracellular vesicles in the original extracellular vesicle sample]-[Amount of untrapped extracellular vesicles]) x 100 / [Amount of extracellular vesicles in the original extracellular vesicle sample] (%)
[0065] The device according to the present embodiment has a high extracellular vesicle capture rate, and can be suitably used for recovering miRNA contained in extracellular vesicles. The amount of recovered miRNA is preferably 0.10 ng / μL or more, more preferably 0.15 ng / μL or more, particularly preferably 0.20 ng / μL, and most preferably 0.25 ng / μL. The amount of recovered miRNA is measured by the method described in the Examples below.
[0066] When protrusions are fabricated by utilizing crystal growth (see, for example, Patent Document 1), the material of the protrusions is limited to certain materials such as zinc oxide, making it difficult to flexibly change the material depending on the type of biological sample to be captured. In contrast, in the device according to the present embodiment, the protrusions 5 are formed by the exposed parts 4b of the irregularly shaped particles 4 from the polymer layer 3, so that it is possible to change the material of the protrusion surface depending on the type of biological sample to be captured, and a high capture efficiency can be achieved for various biological samples.
[0067] The device according to this embodiment can be produced, for example, by a method including the following steps (1) to (3). [1] A step of applying a coating liquid containing irregularly shaped particles 4, a polymer, a poor solvent for the polymer, and a good solvent for the polymer to a supporting substrate 1 to form a coating film. [2] A process to volatilize the good solvent for the polymer from the coating film and make the polymer insoluble [3] A step of volatilizing the poor solvent for the polymer from the coating film in which the polymer has been insolubilized.
[0068] <Process [1]> In step [1], a coating film is formed by applying a coating liquid to a supporting substrate 1. There are no particular limitations on the method for applying the coating liquid to the supporting substrate 1, and various commonly known methods such as brush coating, dip coating, spin coating, bar coating, flow coating, spray coating, roll coating, air knife coating, blade coating, gravure coating, microgravure coating, and slot die coating can be used.
[0069] (Poor solvent for polymers) A "poor solvent for a polymer" refers to a liquid that does not dissolve or is poorly soluble in the polymer. When a powdered polymer is placed in a liquid and stirred for 24 hours, and the solid is recovered from the liquid and dried, if the weight loss from the original polymer is less than 50%, the liquid is a poor solvent for the polymer.
[0070] When the coating liquid contains a poor solvent for the polymer, the polymer becomes insoluble when the good solvent for the polymer evaporates, and the irregularly shaped particles 4 are fixed. When the good solvent for the polymer evaporates, the presence of a poor solvent prevents the irregularly shaped particles 4 from being exposed above the liquid surface, and the particles are fixed in this state, making it possible to suppress particle aggregation. As a result, protrusions 5 are formed on the surface of the coating layer 2 with high uniformity. If the coating liquid does not contain a poor solvent, the irregularly shaped particles 4 are not fixed when the good solvent evaporates, and the particles aggregate, resulting in areas where protrusions 5 are not formed, or variation in the structure of the protrusions 5.
[0071] The poor solvent for the polymer preferably has a fluorine group (-F). In this case, when the surface tension of the poor solvent for the polymer decreases and the good solvent for the polymer volatilizes, a two-layer structure is more likely to be formed, with the poor solvent for the polymer in the upper layer of the coating liquid and the insoluble polymer in the lower layer. This makes it easier to form a structure in which the polymer fixes the bases of the irregularly shaped particles 4, making it possible to form protrusions 5 with high strength.
[0072] The poor solvent for the polymer having a fluorine group is not particularly limited as long as it is a poor solvent for the polymer having a fluorine group, and examples thereof include monofluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, hexafluorobenzene, octafluorocyclopentene, hexafluoroisopropyl methyl ether, octafluorotoluene, tetradecafluoromethylcyclohexane, eicosafluorononane, octafluorooctane, 1,3-bis(trifluoromethyl)benzene, tetradecafluoro-2-methylpentane, hexafluoromethylcyclohexane ... Decafluoro-n-octyl bromide, tetradecafluorohexane, pentadecafluorotriethylamine, hexacosafluorododecane, hexadecafluoroheptane, hexadecafluoro(1,3-dimethylcyclohexane), heptacosafluorotributylamine, octadecafluorodecahydronaphthalene perfluorodecalin, perfluoro(2-butyltetrahydrofuran), perfluorotriamylamine, 1,1,2-trichlorotrifluoroethane, 1,2-dichlorotetrafluoroethane, 1,3-dichlorotetrafluoropropane Pan, 1-chloro-1,2,2,2-tetrafluoroethane, 1-bromo-1,1,2,2-tetrafluoroethane, 1-fluoro-1,2-dichloroethane, 1-fluoro-2,2,3,3-tetrachloropropene, 1-fluoro-2,2,3,3-tetrafluoropropene, 1-fluoro-2,3,3,3-tetrachloropropene, 1-fluoro-3,3-dichloropropene, 1-fluoro-4-chloro-2-nitrobenzene, 1,1,1-trifluoroethane, 1,1,2-trichloro-1,2,2-trifluoroethane, 1,1-dichloro- 1-Fluoroethane, 1,1-dichloro-2,2,2-trifluoroethane, 1,2,2-trifluoroethane, 1,2-dichloro-1,1,2,2-tetrafluoroethane, 1,2-dichloro-1,2,2-trifluoroethane, 1,2-dichloro-1,2,2-trifluoroethanol, 1,2-difluoro-1,2-dichloroethylene, 1,2-difluoroethane, 1,3-dichloro-1,1,2,2-tetrafluoroethane, 1,3-dichloro-1,2,2-trifluoropropane, 1,4-difluorobenzene, 2,2-dichloro-1,1,Examples of the fluorocarbon include 1-trifluoroethane, 2,2-difluoroethane, 2,3-difluoro-1,1,2,2-tetrachloroethane, 2,3-difluoro-1,1,2,2-tetrafluoroethane, 2,4-difluorobenzene, 3,3-dichloro-1,1,1-trifluoropropene, 3,3-dichloro-1,1,2,2-tetrafluoropropene, 3,3-difluoro-1,2-dichloropropene, 3,3-difluoro-1,2-epoxypropane, and 3,4-difluoro-1,1,2,2-tetrachloroethane.
[0073] The surface tension of the poor solvent for the polymer is preferably 22 mN / m or less. By having a surface tension of 22 mN / m or less, the poor solvent is likely to gather on the surface of the coating layer 2, and a two-layer structure of the poor solvent and the polymer is likely to be formed. The surface tension of the poor solvent for the polymer is more preferably 20 mN / m or less, even more preferably 18 mN / m or less, and most preferably 16 mN / m or less. From the viewpoint of suppressing the influence of environmental destruction when discharged into the environment, a higher surface tension is preferable, and therefore the surface tension is preferably 13 N / m or more, more preferably 15 N / m or more, even more preferably 17 N / m or more, and most preferably 19 N / m or more.
[0074] The boiling point of the poor solvent for the polymer is preferably 200° C. or less, 175° C. or less, or 150° C. or less under atmospheric pressure in order to reduce the drying time of the coating, and may be 140° C. or less, 130° C. or less, 120° C. or less, or 100° C. or less. The boiling point of the poor solvent for the polymer is higher than the boiling point of the good solvent for the polymer under atmospheric pressure, and may be 80° C. or more, 90° C. or more, 100° C. or more, or 110° C. or more.
[0075] The content of the poor solvent for the polymer may be 1.0 mass% or more, 2.0 mass% or more, 3.0 mass% or more, 4.0 mass% or more, 5.0 mass% or more, or 6.0 mass% or more, and may be 20.0 mass% or less, 15.0 mass% or less, 12.0 mass% or less, 10.0 mass% or less, 8.5 mass% or less, or 7.0 mass% or less, based on the total mass of the coating liquid.
[0076] (Good solvent for polymers) A "good solvent for a polymer" refers to a liquid that dissolves the polymer. When a powdered polymer is placed in a liquid and stirred for 24 hours, and the solid is then recovered from the liquid and dried, if the weight of the original polymer is reduced by 50% or more, the liquid is a good solvent for the polymer.
[0077] By including a good solvent for the polymer, the polymer remains dissolved in the coating liquid before application, which improves the uniformity of the coating (coating film). If the coating liquid does not include a good solvent for the polymer, the insolubilized polymer solid and irregularly shaped particles 4 remain dispersed in the coating liquid, and the coated irregularly shaped particles 4 cannot be fixed to the substrate, resulting in a decrease in the strength of the protrusions 5. The good solvent evaporates first, forming the two-layer structure of the poor solvent and polymer mentioned above, and therefore the boiling point of the good solvent is lower than that of the poor solvent.
[0078] The difference (T3-T4) between the boiling point T3 of the poor solvent for the polymer under atmospheric pressure and the boiling point T4 of the good solvent for the polymer under atmospheric pressure is preferably 10° C. or more, more preferably 20° C. or more, and most preferably 30° C. or more, since this facilitates the formation of a two-layer structure of the poor solvent and the polymer and is more suitable for increasing the strength of the protrusions 5. If the boiling point is too low, it may cause the coating liquid to dry out during storage, so T3-T4 is preferably 70° C. or less or 50° C. or less, and may be 40° C. or less, 30° C. or less, or 10° C. or less.
[0079] The boiling point of a good solvent for the polymer under atmospheric pressure may be 90°C or lower, 80°C or lower, 70°C or lower, 60°C or lower, 50°C or lower, or 40°C or lower, or may be 30°C or higher, 40°C or higher, 50°C or higher, or 60°C or higher.
[0080] Suitable solvents for the polymer include methyl ethyl ketone, dimethylformamide, acetone, tetrahydrofuran, toluene, and ethyl acetate.
[0081] The content of the good solvent for the polymer may be 50 mass % or more, 60 mass % or more, or 70 mass % or more, and may be 90 mass % or less, 85 mass % or less, or 80 mass % or less, based on the total amount of the coating liquid.
[0082] <Process [2]> In step (2), the good solvent for the polymer is volatilized from the coating film to insolubilize the polymer. By insolubilizing the polymer, a two-layer structure consisting of a poor solvent for the polymer and a polymer layer 3 containing the insolubilized polymer is formed. The polymer layer 3 fixes the irregularly shaped particles 4 onto the support substrate 1.
[0083] The method for volatilizing the good solvent for the polymer is not particularly limited, and various commonly known methods such as heat drying, vacuum drying, air drying, and UV drying can be used.
[0084] <Process [3]> In step [3], the poor solvent for the polymer is volatilized from the coating film in which the polymer has been insolubilized. By removing the poor solvent for the polymer, a coating layer 2 including a polymer layer 3 and irregularly shaped particles 4 fixed to the polymer layer 3 is formed on the support substrate 1, as shown in Fig. 1. Protrusions 5 are formed by exposed portions 4b of the irregularly shaped particles 4 from the polymer layer 3.
[0085] The method for volatilizing the poor solvent for the polymer is not particularly limited, and the above-mentioned drying method for volatilizing the good solvent for the polymer can be applied.
[0086] <Other processes> The method for manufacturing the device according to the present embodiment may further include a step (other step) other than the steps described above. The method for manufacturing the device according to the present embodiment may further include, as another step, a step of covering at least a part of the side of the coating layer 2 on which the protrusions 5 are present, which is formed by volatilizing the poor solvent of the polymer in step [3], with a covering layer. The covering layer and the method for covering with the covering layer may be as described above. When manufacturing a device in the form of a well plate shown in FIG. 4, the method for manufacturing the device may further include a step of bonding a covering substrate 6 (e.g., a bottomless well plate) to the coating layer 2. There is no particular limitation on the method for bonding the covering substrate 6 and the coating layer 2, and a physical or chemical bonding method such as adhesive tape, adhesive, or heat fusion can be used. When manufacturing a device having a flow channel structure shown in FIG. 5, the method for manufacturing the device may further include a step of arranging the above-mentioned intermediate layer 8 and covering substrate 6 in this order on the surface of the coating layer 2 on the side on which the protrusions 5 are present. EXAMPLES
[0087] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the examples and comparative examples, the major axis and minor axis of the irregular particles, the strength, the extracellular vesicle capture rate, and the amount of miRNA were measured by the following methods.
[0088] [Measurement of major and minor diameters of irregularly shaped particles] (Preparation of measurement samples) A measurement sample was prepared by casting and drying the irregular particle dispersion on a collodion-supported copper mesh. The irregular particle dispersion was prepared by adding 10 mg of irregular particles to 1 mL of methanol and dispersing them by ultrasonic irradiation for 10 seconds.
[0089] (measurement) A scanning electron microscope (Keyence VE-9800) was used to obtain a scanning electron microscope photograph of the measurement sample. The long diameter was calculated by measuring the maximum particle size of the irregularly shaped particles on the obtained photograph. The axis in the long diameter direction was taken as the long axis, and the short diameter was calculated by measuring the maximum length in the direction perpendicular to the long axis. The average of the long diameter and short diameter of 50 randomly selected particles was calculated. The calculated long diameter was divided by the short diameter to obtain the ratio of the long diameter to the short diameter (long diameter / short diameter).
[0090] [Measurement of the ratio of protrusion height to major axis of irregularly shaped particles] The surface of the coating layer was embedded in resin, and the cross section was then cut and observed with a scanning electron microscope (Keyence VE-9800). In the scanning electron microscope photograph of the cross section, the distance from the surface of the polymer layer opposite the support substrate to the apex of the protrusion was determined as the height of the protrusion. The height of the protrusion was divided by the major axis of the irregular particles determined by the above-mentioned method to determine the ratio of the height of the protrusion to the major axis of the irregular particles (height of the protrusion / major axis of the irregular particles).
[0091] [Proportion of area with protrusions] The surface of the coating layer was measured using a scanning electron microscope (Keyence VE-9800). On the obtained micrograph of the surface of the coating layer, the area where irregular particles were present was binarized as white and the area where they were not present was black, and the ratio of the white area was calculated. This was taken as the ratio of the area of the area where the protrusions were present to the entire coating layer when the coating layer was viewed from the side where the protrusions were present.
[0092] [Strength check] The strength of the coating layer was evaluated by scratching the coating surface five times with a Bencot (manufactured by Asahi Kasei Corporation) under a load of 50 g, and checking for peeling of the coating layer from the supporting substrate both visually and using a scanning electron microscope. ◯: No peeling of the coating layer. ×: Peeling of the coating layer occurred.
[0093] [Measurement of extracellular vesicle capture rate and miRNA amount] The medium in which the cells were cultured was used as the extracellular vesicle sample. When the device was a 24-well plate, the extracellular vesicle sample was dropped at 250 μL / well and left to stand overnight. The supernatant was collected and the extracellular vesicle concentration was measured to determine the amount of extracellular vesicles that were not captured. Lysis buffer was dropped at 250 μL / well and left to stand for 5 minutes. The lysis buffer was collected and purified using a nucleic acid purification kit, after which the miRNA concentration was measured.
[0094] When the device was a flow channel, 250 μL of the sample was passed through the flow channel, the solution was collected, and the extracellular vesicle concentration was measured to determine the amount of extracellular vesicles that were not captured. Next, 250 μL of lysis buffer was passed through the flow channel, the solution was collected, and after purification with a nucleic acid purification kit, the miRNA concentration was measured. The extracellular vesicle capture rate was calculated using the following formula. ([Amount of extracellular vesicles in the original extracellular vesicle sample] - [Amount of untrapped extracellular vesicles]) x 100 / [Amount of extracellular vesicles in the original extracellular vesicle sample] (%)
[0095] [Example 1] 0.5 g of zinc oxide irregular particles (Sigma-Aldrich; major axis 0.3 μm, minor axis 0.05 μm, major axis / minor axis ratio 6.0) was added to 10 mL of methanol and dispersed by ultrasonic irradiation. 0.05 g of methacryloxypropyltrimethoxysilane (Tokyo Chemical Industry) (solubility parameter 12.5) and 0.05 g of 25% ammonia water (Fujifilm Wako Pure Chemical) were added and stirred at 300 rpm using a stirrer at 60 ° C for 2 hours. After the reaction, the mixture was filtered through a 106 μm mesh filter to remove coarse aggregates, and the supernatant was collected by decantation. Methanol was added to the collected particles and centrifuged at 4000 rpm for 10 seconds, the supernatant was discarded, and the particles were washed again with methanol. The particles were then dried at room temperature to obtain irregular particles whose surfaces were modified with methacryloyl groups (solubility parameter 9.5).
[0096] 10 parts by mass of the irregularly shaped particles surface-modified with methacryloyl groups, 2.5 parts by mass of polymethyl methacrylate, and 7.5 parts by mass of 1,3-bis(trifluoromethyl)benzene were added to 50 parts by mass of methyl ethyl ketone and mixed. The particles were dispersed by ultrasonic irradiation. A coating layer consisting of irregularly shaped particles and a polymer layer was formed by spin-coating the particle dispersion liquid on a polycarbonate film (manufactured by Teijin; product name Panlite) at 1000 rpm for 30 seconds. The surface of this coating layer was coated with zinc oxide to a thickness of 100 nm by sputtering. Figure 6 shows a scanning electron microscope photograph of the device surface of Example 1.
[0097] The support substrate having the above coating layer was attached to the bottom of a bottomless 24-well plate to produce a device having a protrusion structure on the bottom of the well. The device was packaged in a sterilization bag and sterilized with ethylene oxide gas. After aeration for 24 hours, the device was removed and used for evaluation.
[0098] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 89.4%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.201ng / μL, indicating that a large amount of miRNA could be recovered.
[0099] [Example 2] The irregular-shaped particles used were zinc oxide irregular-shaped particles (Sigma-Aldrich; major axis 1 μm, minor axis 0.18 μm, major axis / minor axis ratio 5.6), and the rest of the procedure was the same as in Example 1 to fabricate a device. Figure 7 shows a scanning electron microscope photograph of the surface of the device of Example 2.
[0100] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 90.1%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.239 ng / μL, indicating that a large amount of miRNA could be recovered.
[0101] [Example 3] The irregular-shaped particles used were zinc oxide irregular-shaped particles (Sigma-Aldrich; major axis 4.5 μm, minor axis 0.2 μm, major axis / minor axis ratio 22.5), and the rest of the procedure was the same as in Example 1 to fabricate a device. Figure 8 shows a scanning electron microscope photograph of the surface of the device of Example 3.
[0102] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 82.5%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.226 ng / μL, indicating that a large amount of miRNA could be recovered.
[0103] [Example 4] A device was produced in the same manner as in Example 1, except that irregular-shaped particles of titanium oxide (manufactured by Sigma-Aldrich; major axis 10 μm, minor axis 0.1 μm, major axis / minor axis ratio 100) were used.
[0104] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 92.2%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.104ng / μL, indicating that a large amount of miRNA could be recovered.
[0105] [Example 5] The coating layer surface was sputtered with alumina oxide, and otherwise the device was fabricated in the same manner as in Example 3. Figure 9 shows a scanning electron microscope photograph of the device surface of Example 4.
[0106] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 92.1%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.14 ng / μL, indicating that a large amount of miRNA could be recovered.
[0107] [Example 6] A device was fabricated in the same manner as in Example 3, except that the surface of the coating layer was sputtered with silica.
[0108] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 91.9%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.128ng / μL, indicating that a large amount of miRNA could be recovered.
[0109] [Example 7] The surface of the coating layer was sputtered with nickel oxide, and otherwise the device was fabricated in the same manner as in Example 3.
[0110] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 92.3%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.203ng / μL, indicating that a large amount of miRNA could be recovered.
[0111] [Example 8] The surface of the coating layer was sputtered with tin oxide, and otherwise the device was fabricated in the same manner as in Example 3.
[0112] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 94.9%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.156 ng / μL, indicating that a large amount of miRNA could be recovered.
[0113] [Example 9] The surface of the coating layer was sputtered with titanium oxide, and the rest of the process was the same as in Example 3 to fabricate a device.
[0114] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 92.6%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.1 ng / μL, indicating that a large amount of miRNA could be recovered.
[0115] [Example 10] The surface of the coating layer was sputtered with yttria oxide, and the rest of the process was the same as in Example 3 to fabricate a device.
[0116] The fabricated device had excellent projection strength and an extracellular vesicle capture rate of 88.1%, demonstrating excellent extracellular vesicle capture performance.
[0117] [Example 11] The device was fabricated in the same manner as in Example 3, except that the surface of the coating layer was sputtered with indium tin oxide.
[0118] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 93.7%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.468ng / μL, indicating that a large amount of miRNA could be recovered.
[0119] [Example 12] A device was produced in the same manner as in Example 3, except that the sputtering in Example 3 was not carried out and instead a cationic polymer was coated by the following method.
[0120] After forming the coating layer, the surface was subjected to plasma treatment using a vacuum plasma device (Vacuum Device Co., Ltd.; PIB-20). The sample was immersed in a 1 mg / mL polydiallyldimethylammonium chloride aqueous solution (Sigma-Aldrich Co., Ltd.) for 10 seconds, washed with pure water, and dried with air.
[0121] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 79.9%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.14 ng / μL, indicating that a large amount of miRNA could be recovered.
[0122] [Example 13] A device was produced in the same manner as in Example 3, except that the sputtering in Example 3 was not carried out and instead an ionic polymer was coated by the following method.
[0123] After forming the coating layer, the surface was subjected to plasma treatment using a vacuum plasma device (Vacuum Device; PIB-20). The film was immersed in a 1 mg / mL polydiallyldimethylammonium chloride aqueous solution (Sigma-Aldrich) for 10 seconds, washed with pure water, and dried with air. The film was further immersed in a 1 mg / mL polystyrene sulfonic acid aqueous solution (Sigma-Aldrich) for 10 seconds, washed with pure water, and dried with air.
[0124] The fabricated device had excellent protrusion strength. In addition, the extracellular vesicle capture rate was 58.8%, indicating excellent extracellular vesicle capture performance. In addition, the amount of miRNA that could be recovered was 0.176 ng / μL, indicating that a large amount of miRNA could be recovered.
[0125] [Example 14] After forming a coating layer in the same manner as in Example 4, instead of bonding a 24-well plate and a film, an adhesive tape and an acrylic plate were attached on the coating layer to fabricate a microchannel having a protrusion structure on the bottom surface. The adhesive tape used had a rectangular through-area of 2 mm x 20 mm and a thickness of 0.1 mm. The acrylic plate used had a circular through-hole with a diameter of 1 mm. The microchannel formed had a channel width of 2 mm, a channel length of 20 mm, and a channel height of 0.1 mm.
[0126] The fabricated device had excellent projection strength and an extracellular vesicle capture rate of 48.3%, demonstrating excellent extracellular vesicle capture performance.
[0127] [Example 15] A coating layer was formed in the same manner as in Example 7, and then a microchannel type device was produced in the same manner as in Example 14.
[0128] The fabricated device had excellent projection strength and an extracellular vesicle capture rate of 51.7%, demonstrating excellent extracellular vesicle capture performance.
[0129] [Example 16] A coating layer was formed in the same manner as in Example 8, and then a microchannel type device was produced in the same manner as in Example 14.
[0130] The fabricated device had excellent projection strength and an extracellular vesicle capture rate of 58.2%, demonstrating excellent extracellular vesicle capture performance.
[0131] [Example 17] A coating layer was formed in the same manner as in Example 9, and then a microchannel type device was produced in the same manner as in Example 14.
[0132] The fabricated device had excellent projection strength and an extracellular vesicle capture rate of 58.5%, demonstrating excellent extracellular vesicle capture performance.
[0133] [Example 18] A coating layer was formed in the same manner as in Example 10, and then a microchannel type device was produced in the same manner as in Example 14.
[0134] The fabricated device had excellent projection strength and an extracellular vesicle capture rate of 60.4%, demonstrating excellent extracellular vesicle capture performance.
[0135] [Example 19] A coating layer was formed in the same manner as in Example 11, and then a microchannel type device was produced in the same manner as in Example 14.
[0136] The fabricated device had excellent projection strength and an extracellular vesicle capture rate of 67.7%, demonstrating excellent extracellular vesicle capture performance.
[0137] [Comparative Example 1] The polycarbonate film was used as it was, without forming a coating layer or performing sputtering, and was attached to a bottomless 24-well plate in the same manner as in Example 1.
[0138] The fabricated device had an extracellular vesicle capture rate of 46.0%, which was a poor capture rate.
[0139] [Comparative Example 2] A microchannel was fabricated in the same manner as in Example 14, without forming a coating layer or performing sputtering, and using the polycarbonate film as it was.
[0140] The fabricated device had an extracellular vesicle capture rate of 41.3%, which was a poor capture rate.
[0141] [Comparative Example 3] A smooth film of zinc oxide was formed on the surface of the polycarbonate film by sputtering without forming a coating layer, and then a microchannel was fabricated in the same manner as in Example 14.
[0142] The fabricated device had an extracellular vesicle capture rate of 38.5%, which was a poor capture rate.
[0143] [Comparative Example 4] When forming the coating layer in Example 3, a solution containing no polymethyl methacrylate was used to form a coating layer without a polymer layer, and the device was otherwise fabricated in the same manner as in Example 3.
[0144] The device produced had poor projection strength.
[0145] The abbreviations in Table 1 are as follows. PC: polycarbonate, PMMA: polymethylmethacrylate, ZnO: zinc oxide, Al2O3: alumina oxide, SiO2: silica, SnO: tin(II) oxide, NiO: nickel oxide, TiO2: titanium oxide, Y2O3: yttria oxide, ITO: indium tin oxide, PDDA: polydiallyldimethylammonium chloride, PSS: polystyrene sulfonate
[0146] The silane coupling agent used in Examples 1 to 19 and Comparative Examples 1 to 4 had a methacryloyl group. The difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer was 3.2.
[0147] [Table 1]
[0148] As shown in Table 1, the device of the embodiment in which protrusions were formed by irregularly shaped particles having portions embedded in the polymer layer and portions exposed from the polymer layer was shown to have excellent protrusion strength and extracellular vesicle capture rate. [Explanation of symbols]
[0149] 1...support substrate, 2...coating layer, 3...polymer layer, 4...irregular particle, 4a...portion embedded in polymer layer, 4b...portion exposed from polymer layer, 5...projection, 6...coated substrate, 7, 7a, 7b...space, 8...intermediate layer, 9...flow path, 10, 10A, 10B...device, S...minor axis of irregular particle, L...major axis of irregular particle
Claims
1. A coating layer is formed on a supporting substrate, the coating layer includes a polymer layer and irregularly shaped particles, the irregular-shaped particles have portions embedded in the polymer layer and portions exposed from the polymer layer, the exposed portions of the polymer layer form protrusions on a surface of the coating layer opposite the supporting substrate.
2. The major axis of the irregular shaped particles is 0.1 to 100 μm. The minor axis of the irregular shaped particles is 0.01 to 10 μm, The device according to claim 1 , wherein the ratio of the major axis of the irregularly shaped particle to the minor axis of the irregularly shaped particle is 2.0 or more.
3. The device according to claim 1 or 2, wherein the ratio of the height of the protrusions to the major axis of the irregularly shaped particles is 0.10 to 0.
95.
4. 3. The device according to claim 1, wherein when the coating layer is viewed from the side where the protrusions are present, the ratio of an area of the region where the protrusions are present to an area of the entire coating layer is 10% or more.
5. The device according to claim 1 or 2, wherein the number of the irregular-shaped particles that do not have a portion embedded in the polymer layer is 50% or less of the total number of the irregular-shaped particles.
6. The device according to claim 1 or 2, wherein a length in an out-of-plane direction of the supporting substrate from the surface of the supporting substrate facing the coating layer to the apex of the protrusion is equal to or less than a major axis of the irregular-shaped particle.
7. The device of claim 1 or 2, wherein the protrusions are oriented in one direction.
8. The device according to claim 1 or 2, wherein the material of the irregularly shaped particles is selected from the group consisting of silica, zinc oxide, titanium oxide, nickel oxide, alumina oxide, yttria oxide, tin oxide, indium oxide, indium tin oxide, silicon carbide, gold, silver, carbon, silicon nitride, and combinations thereof.
9. the irregular-shaped particles are surface-modified with a silane coupling agent at least at the embedded portion; The device according to claim 1 or 2, wherein the difference between the solubility parameter of the silane coupling agent and the solubility parameter of the polymer layer is 5 or less.
10. 3. The device according to claim 1 or 2, wherein the protrusions are coated with a coating layer containing at least one selected from the group consisting of zinc oxide, titanium oxide, nickel oxide, yttria oxide, tin oxide, alumina oxide, silica, indium oxide and indium tin oxide.
11. The device according to claim 1 or 2, wherein the protrusions are coated with a coating layer containing a cationic polymer.
12. The device further comprises a coated substrate having one or more through holes on a surface of the coating layer opposite the supporting substrate; The device according to claim 1 or 2, wherein at least one of the through-holes forms a space for adding a biological sample.
13. the device further comprising an intermediate layer between the coating layer and the coated substrate; The device of claim 12 , wherein the intermediate layer includes an area that bonds the coating layer to the coated substrate and an interior space that forms a flow path for transporting the biological sample.
14. 3. The device according to claim 1 or 2, for collecting a biological sample.
Citation Information
Patent Citations
Biomolecule extraction chip and method for manufacturing biomolecule extraction chip
JP6606786B2
